2022
DOI: 10.1039/d1sc04708f
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Cu morphology on Ru-passivated and Ru-doped TaN surfaces – promoting growth of 2D conducting copper for CMOS interconnects

Abstract: Prolonging the lifetime of Cu as level 1 and level 2 interconnect metal in future nanoelectronic devices is a significant challenge as device dimensions continue to shrink and device structures...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 63 publications
2
12
0
Order By: Relevance
“…3D metal growth is undesirable in many applications, in particular in microelectronics manufacturing. For instance, it is known that, in general, the Cu films deposited as interconnects by ALD exhibit significantly increased resistivity, allegedly because they form nonconducting islands rather than smooth conducting films . Ideal ALD processes provide conformal 2D films, but in the case of Cu deposition on silicon oxide substrates that appears to be difficult to attain.…”
Section: Discussionmentioning
confidence: 99%
“…3D metal growth is undesirable in many applications, in particular in microelectronics manufacturing. For instance, it is known that, in general, the Cu films deposited as interconnects by ALD exhibit significantly increased resistivity, allegedly because they form nonconducting islands rather than smooth conducting films . Ideal ALD processes provide conformal 2D films, but in the case of Cu deposition on silicon oxide substrates that appears to be difficult to attain.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the ratios of metals in the material can be used to further tune the material to have low resistivity and good wettability while maintaining strong barrier properties. This type of work also includes our work on Ru-doped TaN which demonstrated that Cu wetting can be promoted on TaN surfaces by incorporating a known liner material and provides the foundation for the work presented in this paper [29][30][31].…”
Section: Introductionmentioning
confidence: 95%
“…In our previous work [29][30][31] we showed that by doping Ru atoms into the top layer of a TaN surface, a single material with both barrier and liner properties can be created. Such a material can be deposited using ALD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microelectronic manufacturing community has shown great interest in recent years in finding ways to deposit thin ruthenium films for use in developing metal interconnects (either as diffusion barriers for Cu or as the conducting material itself) , as well as to introduce seed layers for electroplating, electrodes in capacitors and dynamic random access memory (DRAM) devices, and gate metals in transistors, , among other applications. Because of the complex topography and small dimensions of the features in the surfaces of modern microelectronics circuits, thin films with great conformality are required, and one of the most promising routes to achieve that is the use of atomic layer deposition (ALD). …”
Section: Introductionmentioning
confidence: 99%